Ketahanan Budaya di Era Modern: Analisis Antropologis terhadap Tradisi Debus Banten - Muhammad Hakiki, Kiki; Muttaqien, Zaenal; Badruzaman, Badruzaman (Ri'ayah: Jurnal Sosial dan Keagamaan, 2024)
Today, Banten's Debus Tradition faces many problems. The process of urbanization, globalization, and the transformation of social values have increased the pressure on this traditional practice. The focus of this research is to uncover the ways the Banten Debus community preserves and adapts itself when facing problems. Evaluating the various methods of preservation and adaptation is the main objective of this research. In addition, this research shows how important government policies, community initiatives and the participation of the younger generation are. Using participatory observation, in-depth interviews, and document analysis, this study collected thorough data on the current state of Debus. The results show that incorporating Debus into the local content material of the school curriculum, securing financial and logistical support, and encouraging it through digital media are crucial for its sustainability. In addition, there are great possibilities to revive interest in the Debus tradition through the active engagement of the younger generation in Debus through digital platforms and social media. This study found that in order to preserve and develop Debus sustainably, a multifaceted approach involving collaboration between community members, cultural institutions and the government is essential. The results show how important it is to use adaptive strategies to maintain cultural heritage when modernization is taking place.